Facile synthesis of oil adsorbent carbon microtubes by pyrolysis of plant tissues - Zhao, Wu (2020)
Inspired by the nature of plant tissue, carbon nanomaterials such as nanofibers have been synthesized by pyrolysis of plant tissues. However, it is challenging in synthesis of tubular structure by pyrolysis because the structure is dynamical non-steady state and always collapses in carbonization process. Herein, carbon microtubes were synthesized by a simple carbonization method-based kapok. The tubular structure with the diameter ranges from 5 to 20 μm was obtained from the final carbon samples, which shows the similar structure with kapok precursors, while the weight was lost about 90%. We demonstrated that the carbon microtubes have excellent performance in oil adsorption with the adsorption capacity of ~ 190 g g−1, which is 1.5 times larger than that of raw kapok. We found that it is reusable for more than ten times in oil adsorption application, and the adsorption capacities of carbon microtubes significantly enhanced when the temperature increased in carbonization.